Symbolic and Quantitative Approaches to Reasoning with Uncertainty 12th European Conference, ECSQARU 2013, Utrecht, The Netherlands, July 8-10, 2013. Proceedings - Gaag, Linda C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 12th European Conference on Symbolic and Quantitative Approaches to Reasoning with Uncertainty, ECSQARU 2013, held in Utrecht, The Netherlands, in July 2013. The 44 revised full papers presented were carefully reviewed and selected from 89 submissions. Papers come from researchers interested in advancing the technology and from practitioners using uncertainty techniques in real-world applications. The scope of the ECSQARU conferences encompasses fundamental issues, representation, inference, learning, and decision making in qualitative and numeric uncertainty paradigms.
Keywords: Computer science; Computer Communication Networks; Logic design; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Information Storage and Retrieval; Computer Communication Networks